Case report: Diagnosis, management and evolution of a bulky and invasive cardiac mass complicated by complete atrioventricular block - Bohbot, Yohann; Garot, Jérôme; Danjon, Isabelle; Thébert, Dominique; Nahory, Louis; Gros, Philippe; Salerno, Fiorella; Garot, Philippe (Frontiers in Cardiovascular Medicine, 2023)
Introduction Cardiac lymphoma is a rare but serious disease that is usually located in the right heart. The symptoms (dyspnea, respiratory distress, fatigue, syncope…) are not specific and depend on the mass location. Cardiac magnetic resonance has a crucial role in the diagnostic strategy but biopsy is mandatory to confirm the diagnosis. Case presentation We report the case of a 63-yeart old man who presented with severe dyspnea and complete atrioventricular block (AVB). A bulky and invasive mass was found in the left atrium extending to the right atrium through the interatrial septum. A cardiac lymphoma was suspected by cardiac magnetic resonance (CMR) imaging and confirmed by transvenous biopsy. The patient was treated with urgent chemotherapy (R-CHOP) and pacemaker implantation. After 4 cycles of R-CHOP the patient was in complete remission with total disappearance of the mass and return of a spontaneous sinus rhythm. Conclusion lymphoma is a therapeutic emergency as appropriate treatment can lead to complete remission even when the mass is extensive and invasive. Complete AVB is a potentially reversible complication of cardiac lymphoma, and the decision to implant a pacemaker must be carefully weighed.